ANTIOXIDANT CORRECTION OF GASTRIC MUCOSAL MORPHOLOGICAL ALTERATIONS IN BACKGROUND CHEMICAL INJURY USING THE PHYTOGENIC AGENT GULIMSAR (International journal of medical sciences, 2026)
Oxidative stress represents a pivotal pathogenetic mechanism underlying gastric mucosal injury induced by chemical and toxic agents. Excessive generation of reactive oxygen species (ROS) disrupts epithelial integrity, impairs microcirculation, and triggers inflammatory cascades, ultimately compromising mucosal regeneration.